The Phylogeography of Rhizophora in Peninsular Malaysia: High Genetic Variation between West and East - Aboubakr, Anwar E. (Scientific Journal for Faculty of Science-Sirte University, 2022)
Geographic history of Rhizophora species and hybrid is effect on their genetic structure. In addition, determining population genetic variation is essential for phylogeography research. For this phylogeography investigation, Four natural population of Rhizophora were collected from five different regions in peninsular Malaysia for this phylogeography study. This study aims to evaluate the genetic diversity of Rhizophora species namely Rhizophora apiculata , Rhizophora mucronata , Rhizophora stylosa and hybrid R. × lamarcki and clarify their genetic structure of its populations using Nucleotide polymorphism in chloroplast intergenic spacer between trnL and trnF genes was studied.The populations of Rhizophora species and hybrids were divided into two groups: the east coast populations, which were represented by samples collected from Mersing, Tanjang Piai, and Sedili; and the west coast populations, which were represented by samples collected from Mersing, Tanjang Piai, and Sedili. The population of the west coast was the second cluster. This result was supported by UPGMA analysis using MEGA5 software.